CSIG-30. miR-146a INHIBITS TUMORIGENESIS AND INDUCES TEMOZOLOMIDE SENSITIVITY VIA AFFECTING CANCER STEM CELL PROPERTIES IN GBM. (11th November 2019) - Cui, Tiantian; Hlavin Bell, Erica; McElroy, Joseph; Liu, Kevin; Manchanda Gulati, Pooja; Johnson, Benjamin; Sebastian, Ebin; Paixao Becker, Aline; Geurts, Marjolein; Gray, Ashley; Meng, Wei; Fleming, Jessica; et al.
Abstract: BACKGROUND: Glioblastomas (GBMs) are the most aggressive primary brain tumors, with an average survival time of less than 15 months. miRNAs are emerging as promising and novel biomarkers in GBM. The aims of this study are: 1) to investigate novel miRNAs biomarkers that affect tumorigenesis and therapeutic sensitivity, and 2) to study the underlying molecular mechanisms in GBM. METHODS: Nanostring v3 was performed followed by univariable (UVA) and multivariable (MVA) analyses. Functional studies were conducted to define the role of miR-146a in GBM tumorigenesis and therapeutic response and the molecular mechanisms were investigated. RESULTS: UVA analyses demonstrated that miR-146a is one of the top miRNAs that correlated with better prognosis in GBM patients (p=9.21E-05), which was independent of MGMT promoter methylation by MVA analyses (p< 0.001). miR-146a expression was significantly downregulated in recurrent GBM tumors compared with the paired primary GBM tumors (p=0.003). Overexpression of miR-146a significantly inhibited tumor cell growth and sensitized patient-derived primary GBM cells to temozolomide (TMZ) treatment in vitro, and showed statistically significant smaller tumor size (p< 0.01) and prolonged survival (p=0.001) in vivo. In addition, miR-146a is downregulated in glioma cancer stem cells, and overexpression of miR-146a significantly affected glioma cancer stem cell self-renewal. We also found that overexpression of miR-146a significantly inhibited the NF-κB, AKT, and ERK pathways. CONCLUSION: Our data suggest, for the first time, that miR-146a predicts favorable prognosis for GBM patients and sensitizes primary GBM cells to TMZ treatment in vitro and in vivo through regulating glioma stem cells. Importantly, miR-146a may prove to be a master switch shutting off AKT, NF-κB, as well as other pathways and may overcome redundancies among these pathways leading to resistance. FUNDING: Bohnenn Fund (to PR), R01CA108633, R01CA169368, U10CA180850-01(NCI), Brain Tumor Funders Collaborative Grant, and The Ohio State University CCC (all to AC).